Enhanced serotonin and mesolimbic dopamine transmissions in a rat model of neuropathic pain. (October 2015) - Sagheddu, Claudia; Aroni, Sonia; De Felice, Marta; Lecca, Salvatore; Luchicchi, Antonio; Melis, Miriam; Muntoni, Anna Lisa; Romano, Rosaria; Palazzo, Enza; Guida, Francesca; Maione, Sabatino; Pistis, Marco
Abstract: In humans, affective consequences of neuropathic pain, ranging from depression to anxiety and anhedonia, severely impair quality of life and are a major disease burden, often requiring specific medications. Depressive- and anxiety-like behaviors have also been observed in animal models of peripheral nerve injury. Dysfunctions in central nervous system monoamine transmission have been hypothesized to underlie depressive and anxiety disorders in neuropathic pain. To assess whether these neurons display early changes in their activity that in the long-term might lead to chronicization, maladaptive plasticity and affective consequences, we carried out in vivo extracellular single unit recordings from serotonin neurons in the dorsal raphe nucleus (DRN) and from dopamine neurons in ventral tegmental area (VTA) in the spared nerve injury (SNI) model of neuropathic pain in rats. Extracellular dopamine levels and the expression of dopamine D1, D2 receptors and tyrosine hydroxylase (TH) were measured in the nucleus accumbens. We report that, two weeks following peripheral nerve injury, discharge rate of serotonin DRN neurons and burst firing of VTA dopamine cells are enhanced, when compared with sham-operated animals. We also observed higher extracellular dopamine levels and reduced expression of D2, but not D1, receptors and TH in the nucleus accumbens. Our study confirms that peripheral neuropathy induces changes in the serotonin and dopamine systems that might be the early result of chronic maladaptation to persistent pain. The allostatic activation of these neural systems, which mirrors that already described as a consequence of stress, might lead to depression and anxiety previously observed in neuropathic animals but also an attempt to cope positively with the negative experience. Highlights: We studied dopamine and serotonin neurons in a rat model of neuropathic pain. Neuropathic rats show enhanced serotonin neuron firing rate. Bursting activity of dopamine neurons and dopamine release are also enhanced. Neuropathic rats display allostatic changes in serotonin and dopamine transmission.